PEMBAJAKAN LAUT DI SOMALIA SEBAGAI KEJAHATAN INTERNASIONAL DALAM PERSPEKTIF HUKUM LAUT INTERNASIONAL - Siti Aisyah; Salwa Putri Septiana; Karindra Alvian Nugraha; Delvi Eka Ariyanti; Ismaya Rahailia Nasution; Angela Maranatha Sibarani; Zulpan Syahputa Gulo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Piracy is one of the forms of international crime that threatens maritime security, international trade, and regional stability. One of the regions that has attracted global attention regarding piracy is the waters off Somalia and the Gulf of Aden. The widespread occurrence of piracy in this area is driven by several factors, including weak governance in Somalia, poor economic conditions, prolonged conflicts, and inadequate maritime law enforcement. This study aims to analyze piracy off the coast of Somalia as an international crime from the perspective of international law of the sea and to examine the measures undertaken by the international community to combat it. The research employs a normative legal research method using statutory and conceptual approaches, primarily based on international legal instruments, particularly the United Nations Convention on the Law of the Sea (UNCLOS) 1982. The findings indicate that acts of piracy in Somali waters fulfill the elements of piracy as defined under UNCLOS 1982 and therefore constitute crimes of international concern. Furthermore, the principle of universal jurisdiction grants all states the authority to apprehend, prosecute, and punish pirates regardless of the nationality of the offenders or victims. Various international operations conducted by states and international organizations have contributed significantly to reducing piracy incidents in the Somali region, although challenges related to law enforcement and political instability remain. Therefore, sustained international cooperation is essential to ensure maritime security and prevent the recurrence of piracy in the future.